EHV Converter Station State Identification Technology Based on Cyber-physical Integration - XIAO Yaohui; YU Junsong; LI Weiming; WANG Yufeng; WANG Yongping; XUE Haiping; HUANG Kai; YAO Jinming (Journal of Harbin University of Science and Technology)
Due to the wide range of data sources ， high collection density ， diverse measurement devices and complex communication protocols in the EHV converter station system，it is difficult for the existing technology to accurately identify the complex states of the converter station and its implied fault characteristics. Therefore，this paper proposes an information-physical fusion-based feature identification technology for EHV converter stations. After pre-processing and correlation analysis of image-based multi-source heterogeneous data，the analysis，training and identification of physical and communication faults of converter stations are performed based on the cyber-physical dual-side state operation and migration feature correlation matrix. Example analysis and method comparison based on actual converter station monitoring images are conducted，and the results show that the method outperforms some traditional fault diagnosis and feature identification algorithms and has better diagnostic capability.